(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This is a presentation of the basic principle, operational functions and modules of the software for planning, programming and control of the serial production in the engineering automation system environment. We specified the software provisioning of the particular application and the benefits from its use in the manufacture process. There is a description of the available data bases for the input of the basic technological information about the work-pieces and details and for setting-up of the metal-processing tools. This product traces the technological sequence and the specifics of the production process of machines with computer and numerical control (CNC), the direct connection and dependency of the individual modules within the processing and exchange of the running current information.